Reflections on access: too vulnerable to research?. (February 2015) - Witham, Gary; Beddow, Anna; Haigh, Carol
This paper seeks to highlight the challenges facing researchers when recruiting vulnerable patients to a research study. We explore the difficulties experienced in gatekeeping for a project involving people with dementia, intellectual disabilities and mental health problems who are also having treatment for cancer. It is argued that the challenges in identifying and recruiting vulnerable participants extend beyond ethics committees and governance to the perceptions and judgements of health care professionals in 'allowing' access to particular patient groups. These positions and judgements appear to be embedded in certain construction(s) of cancer and discourses surrounding dementia, intellectual disabilities and mental health.